Meningkatkan Partisipasi Masyarakat Sungai Telang Dalam Pelestarian Hutan - Hamirul, Hamirul; Zulbahrain, Zulbahrain; Pratiwi, Widya; Hidayat, Nanang Al; M., Ariyanto (Jurnal Publisitas, 2020)
Lack of community participation in nature conservation, especially forest preservation, is a separate problem using a descriptive method with a qualitative approach and data collection techniques used by interviews, with 11 informants in total using triangulation analysis techniques. Results of research Participation of local communities, especially those living in and around the Kerinci Seblat national park (TNKS), have a high level of dependency or level of need for potential in the KSNP area, related to community participation in the management of the KSNP area in Sungai Telang Hamlet Bathin III Ulu Subdistrict Bungo Regency Sungai Telang Sub-District Bathin III Ulu Subdistrict Bungo District is still not optimal and can be said to be still low. management of forest resources in the KSNP area besides the community also does not understand the boundaries of the area including TNKS forest, the implementation of forest resource management in the TNKS area, especially with villages that directly border the TNKS area such as Sungai Telang Hamlet, Bathin III District Bungu Ulu District, in this case management tends to safeguard and protect forests carried out by conducting patrols with the community, especially the Forestry Partner Community as a form of community participation, due to the zones contained in the Sungai Telang sub-village TNKS including the jungle zone and core zones that need safeguards and protection from forest destruction activities carried out by unscrupulous people.